The evolution of social (welfare) state model and its influence on the social security of France - Taminskaitė, Gabrielė (Teisė, 2019)
[full article and abstract in Lithuanian; abstract in English]The article examines the preconditions of the formation of social (welfare) state of France since the Great French Revolution (1798) and, its evolution until the modern social (welfare) state model, as well as the influence of the social (welfare) state model of France on the guarantees of the social security and the legal regulation of the Republic of France. The article discusses the theoretical concept of the welfare (social) state, analyses the modern concept of the welfare state in France, and examines the specific guarantees of the social security rights derived from the social (welfare) state concept. The article, moreover, presents conclusions, related to the classification of the social (welfare) state stages of development, and the establishment of basic principles of social security (such as social solidarity) in the French legal system.
Keywords: social (welfare) state; social security; social solidarity; the French legal system